Beyond the Protestant Ethic: Religion, Economic Subjectivity, and Moral Critique in a Post-Weberian World - Pradana, Mahatva Yoga Adi; Faturahman, Muhamad (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
Religious ethics remain entangled with economic conduct even as capitalism becomes increasingly neoliberal and digitally mediated. This article revisits Weber’s account of the Protestant ethic to examine that entanglement under postsecular conditions and asks how non-Western religious practices complicate linear narratives of rationalization, disenchantment, and religious decline. Employing a critical conceptual review, the study purposively synthesizes foundational Weberian works, critical interventions by Asad, Taylor, and Foucault, and contemporary scholarship on neoliberalism, moral economy, Islamic entrepreneurship, digital religion, religious authority, and eco-spirituality. Indonesian studies serve as contextual illustrations rather than representative evidence. The analysis develops three interrelated movements: rationalization, re-enchantment, and the return of the spirit. These movements are not sequential historical stages but processes that may coexist within the same religious-economic practice. The conceptual synthesis indicates that religion is neither external to capitalism nor inherently resistant to it. Religious ethics may reinforce entrepreneurial self-discipline, platform visibility, and market adaptation while also sustaining moral critiques of inequality, commodification, and ecological harm. The article therefore offers a diagnostic framework for examining the ambivalent formation of economic subjectivity across religious and cultural contexts. Because the corpus is purposive and non-exhaustive, the argument is conceptual and does not establish prevalence or causality.